An atypical presentation of a pericardial cyst - Sahni, Dev R (Oxf Med Case Reports, 2017)
A pericardial cyst is a benign and rare congenital anomaly. The presentation of pericardial cysts varies with the extent of mediastinal involvement. Complaints can include dyspnea, pleuritic chest pain and systemic symptoms; however, the majority are asymptomatic. Imaging modalities such as MRI, CT and X-ray can visualize the cysts. Treatment approach includes aspiration or surgical resection. We describe an atypical presentation of a pericardial cyst and subsequent treatment and recommendations for these rare anomalies.